TALABALARDÍŃ MÁDENIYATLARARALÍQ BAYLANÍS KOMPETENCIYASÍN RAWAJLANDÍRÍWDA KREATIV MODULLERDIŃ ROLI - Arzieva, Bibi-Sanem Aynazarovna (SCIENCE and SOCIETY, 2026)
The study compared verbal (proverbs, clan nomenclature) and non-verbal communicative elements of the Karakalpak people with the American and British cultures. The lexicon of modern English (slang, abbreviations, metaphors, borrowings) has been studied from a pragmatic perspective. Based on the pragmalinguodidactic approach, innovative technologies (authentic discourse analysis, role-playing games, contrast analysis, project method) were proposed.